Failure Patterns and Ultimate Load-Carrying Capacity Evolution of a Prestressed Concrete Cable-Stayed Bridge: Case Study. Issue 7 (July 2013) - Yang, Ou; Li, Hui; Ou, Jinping; Li, Q.S.
An approach to analyzing the evolution of the failure patterns and ultimate load-carrying capacity of prestressed concrete (P.C.) cable-stayed bridges based on a mixture of inspection and structural health monitoring (SHM) techniques is proposed. Firstly, a finite element model (FEM) of a bridge structure was established based on the design blueprint and was updated using periodic inspection or SHM data. The relationship between girder section axial force and bending moment bearing capacity was analysed with the consideration of damage and performance deterioration. Then, using vehicle loading patterns, which can be obtained from SHM data or bridge design codes, vehicle loads are applied to the updated FEM to determine the internal forces in bridge components. Finally, the locations where loads exceed the bearing capacity of components are set as plastic hinges to model the nonlinear behaviour of the structure. This procedure is repeated with the load increasing continuously up to the ultimate load-carrying capacity of the bridge. The corresponding FEM at this point gives the failure mode of the bridge. A P.C. cable-stayed bridge with a 260-m main span was employed to validate the proposed approach for 4 representative states (healthy, damaged, strengthened, and re-damaged states). The results presented in this paper confirm the feasibility of the proposed approach, and indicate that durability damage (such as girder cracking and steel bar corrosion), variations in the cable forces, girder shape (i.e., girder deflection) and structural configuration (i.e., boundary condition variations) have significant effects on the failure mode and ultimate load-carrying capacity of the P.C. cable-stayed bridge.